Super-hydrophobic coating with radiation refrigeration function
By adding nanoboro nitride and nanosilicon nitride to the radiation refrigeration coating and modifying it, a low-surface energy hydrophobic coating is formed, which solves the problem that existing coatings are difficult to achieve superhydrophobic properties and long-term durability when improving radiation refrigeration performance, and improves multiple properties of the coating, such as superhydrophobic, self-cleaning, radiation refrigeration and corrosion resistance.
Patent Information
- Application Number
- CN202510107278.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
While improving the radiation refrigeration performance, existing radiation refrigeration coatings are difficult to achieve superhydrophobic properties and long-term durability. The coating has low hardness, poor corrosion resistance and wear resistance, resulting in a short service life.
By adding nanoboro nitride and nanosilicon nitride, and carrying out acid leaching and modified doped titanium dioxide treatment, a low-surface energy hydrophobic coating is formed, and combined with the synergistic effect of silicone modified nanosilicon dioxide, the superhydrophobic properties, acid and alkali corrosion resistance and wear resistance of the coating are improved.
While achieving the superhydrophobic properties, self-cleaning ability and radiation refrigeration function of the coating, it significantly improves acid and alkali corrosion resistance and wear resistance, and extends the service life of the coating.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of radiation cooling coatings, and in particular to a super-hydrophobic coating with radiation cooling and a preparation method thereof. Background Art
[0002] Radiative cooling is a passive cooling technology that uses thermal radiation to achieve cooling. This technology can achieve zero-energy subambient cooling under strong sunlight, and is expected to become an alternative technology to traditional high-energy refrigeration equipment (such as air conditioners), thus helping to alleviate the current increasingly severe energy crisis. The subambient cooling ability of radiative cooling materials comes from the fact that they can emit heat to the cold outer space through the atmospheric transparent window (the material can be called a thermal emitter), while reflecting a large amount of solar radiation heat (i.e., having a high solar emissivity). In recent years, various high-performance radiative cooling materials based on thermal emitters have been developed, mainly used in building energy conservation and personal thermal management. According to the spectral response characteristics of such materials in the mid-infrared band, radiative cooling materials can be mainly divided into two categories: non-selective thermal emitters and selective thermal emitters. Non-selective thermal emitters refer to radiative cooling materials that have high emissivity in the entire mid-infrared band. Selective thermal emitters usually refer to materials that have high selective emissivity only in the 8–13μm atmospheric transparent window band and high reflectivity in the rest of the mid-infrared band. At present, in radiation cooling technology, the radiation cooling performance of the coating is usually improved by adding nanoparticles, but the refractive index of nanoparticles is similar to that of high molecular organic matter, so it is difficult to improve the reflectivity. Patent Publication No.: CN 118994983 A discloses a radiation cooling coating with stain resistance and a preparation method thereof. Through the graft copolymerization reaction of hollow multi-microspheres with silane coupling agent, N-dodecyl acrylamide, and N-vinyl-2-pyrrolidone, a layer of polymer is formed on the surface of the carbon microspheres to obtain modified hollow porous carbon microspheres with a core-shell structure, so that the contact angle between the coating and water can reach about 135°. The hydrophobic ability of the radiation cooling coating of the invention is general, and the static contact angle does not reach the super-hydrophobic standard. Therefore, it is very necessary to achieve the super-hydrophobic performance of the radiation cooling coating while improving the radiation cooling performance of the coating and increase its self-cleaning performance. At the same time, in addition to passive cooling and super hydrophobicity, super self-cleaning ability, super hydrophobic coatings with radiation cooling are generally used on the outer layer of buildings. In addition to sunlight exposure, they will also be subjected to wind and rain, as well as erosion and corrosion by various acidic and alkaline substances or gases in the air. At present, most of the hydrophobic coatings for radiation cooling have low hardness, poor corrosion resistance and wear resistance, resulting in poor durability of the coating and cannot be used for a long time. In summary, although the hydrophobic coatings for radiation cooling have been widely reported, the coatings formed by most of the coatings cannot have excellent hardness, corrosion resistance and wear resistance under the premise of ensuring super hydrophobicity, resulting in a short service life and poor durability of the coating. Summary of the invention
[0003] An object of the present invention is to solve the above-mentioned problem and provide a super hydrophobic coating with radiative cooling, which can form a low surface energy hydrophobic coating through the synergistic effect of adding nano boron nitride, nano silicon nitride and nano silicon dioxide, and has good super hydrophobic properties and good self-cleaning ability, and at the same time has excellent acid and alkali corrosion resistance and wear resistance, and good antioxidant ability.
[0004] To achieve the above purpose, the technical solution provided by the present invention is:
[0005] In a first aspect of the present invention, a super-hydrophobic coating with radiative cooling is provided, wherein the super-hydrophobic coating with radiative cooling comprises the following materials by mass fraction: 1.5-2.2% of nano zinc oxide, 3.9-5.8% of nano aluminum oxide, 1.5-2.2% of alkaline silica sol, 0.3-1% of nano silicon dioxide, 0.3-1% of nitride, 0.3-1% of curing agent, 8.1-12.1% of coupling agent, and 76-83% of solvent; the nano silicon dioxide is acid-leached, and the nitride is a mixture of nano boron nitride and nano silicon nitride in a weight ratio of 2:3.
[0006] Preferably, the acid leaching treatment is carried out using a mixed acid of sulfuric acid and hydrofluoric acid.
[0007] Preferably, the concentrations of the sulfuric acid and the hydrofluoric acid are 15wt% and 10wt% respectively, the sulfuric acid and the hydrofluoric acid are mixed in a weight ratio of 1:1, the treatment time is 1-2 hours, and the treatment temperature is 50-80°C.
[0008] Preferably, the coupling agent includes polydimethylsiloxane, α,ω-dihydroxypolysiloxane, hexamethyldisilazane, methyltrimethoxysilane, γ-aminopropyltriethoxysilane, [perfluoro(polypropoxy)]methoxypropyltrimethoxysilane.
[0009] Preferably, the solvent includes n-butanol, xylene, water, anhydrous ethanol, and glacial acetic acid.
[0010] Preferably, the super-hydrophobic coating with radiation cooling comprises the following materials by mass fraction: 2% nano zinc oxide, 4% nano aluminum oxide, 2% alkaline silica sol, 1% nano silicon dioxide, 0.2% nano silicon nitride, 0.3% nano boron nitride, 0.9% curing agent, 7% polydimethylsiloxane, 0.5% α, ω-dihydroxypolysiloxane, 2% hexamethyldisilazane, 1.5% methyltrimethoxysilane, 0.6% γ-aminopropyltriethoxysilane, 8% n-butanol, 66% xylene, 1% water, 2% anhydrous ethanol, and 1% glacial acetic acid.
[0011] Preferably, the nano boron nitride and nano silicon nitride are nano boron nitride and nano silicon nitride modified by doping titanium dioxide. The preparation of the modified nano boron nitride and nano silicon nitride doped with titanium dioxide includes the following steps: step 1, mixing nano boron nitride, nano silicon nitride and nano titanium dioxide in a weight ratio of 10:1-5, and then calcining at high temperature for 1-3 hours, adding n-hexane and anhydrous ethanol for stirring and ultrasonic dispersion to obtain suspension A, step 2, mixing suspension A with stearic acid in a reactor for reaction for 1-5 hours, separating and drying to obtain the modified nano boron nitride and nano silicon nitride doped with titanium dioxide.
[0012] Preferably, the particle size of the nano-boron nitride and nano-silicon nitride is 0.5-3 μm.
[0013] Preferably, the method for preparing the super hydrophobic coating with radiative cooling comprises:
[0014] S1. Place nano zinc oxide and nano aluminum oxide in a V-type mixer, prepare solution b with hexamethyldisilazane, water and ethanol, atomize solution b and add it into nano zinc oxide and nano aluminum oxide, react for 1-3 hours, and then dry to obtain modified powder;
[0015] S2, preparing alkaline silica sol and n-butanol into sol, uniformly dispersing by ultrasonic, dropping glacial acetic acid into the sol and dispersing by ultrasonic again, adding nano-silicon dioxide, nano-boron nitride, and nano-silicon nitride and dispersing by ultrasonic, adding α,ω-dihydroxypolysiloxane, methyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and reacting at 50-60° C. for 2-6 hours to obtain a mixed sol;
[0016] S3, uniformly mixing polydimethylsiloxane, the modified powder obtained in S1, and xylene, and dispersing them by ultrasonication, and then adding the mixed sol obtained in S2 and dispersing them by ultrasonication to obtain component A;
[0017] S4. Mixing the curing agent as component B and component A uniformly to obtain the super-hydrophobic coating with radiation cooling.
[0018] The beneficial effects of the present invention are as follows:
[0019] (1) The present invention processes nano-silica by acid leaching to form a concave-convex microstructure on the surface, thereby obtaining silica with a large surface area, which is easily modified by siloxane to form super-hydrophobic modified silica, so that the coating formed by the present invention has super-hydrophobic properties, reduces the contact area between pollutants and the coating, and prevents pollutants from adhering to the surface of the coating, thereby having self-cleaning ability.
[0020] (2) The present invention adds nano boron nitride and nano silicon nitride. The nano boron nitride and nano silicon nitride are sintered at high temperature before modification to form oxygen-containing functional groups on their surfaces. Then, titanium dioxide is doped with stearic acid and then grafted and co-chained to increase its inertness so that it has more significant acid and alkali corrosion resistance and wear resistance, and reduce its surface free energy without affecting its dispersibility and compatibility in the coating. Then, the synergistic effect with the siloxane-modified nano silicon dioxide makes the coating of the present invention have ultra-low surface energy when formed. Finally, the coating of the present invention has a radiation cooling function and excellent super-hydrophobic properties, making the coating not easy to be stained with dust, significantly improving the self-cleaning ability of the coating of the present invention, and due to the addition of nano boron nitride and nano silicon nitride, the coating has good acid and alkali corrosion resistance and wear resistance, and antioxidant properties. DETAILED DESCRIPTION
[0021] In one embodiment of the present invention, the present invention provides a super-hydrophobic coating with radiative refrigeration, wherein the super-hydrophobic coating with radiative refrigeration comprises the following materials by mass fraction: 1.5-2.2% of nano zinc oxide, 3.9-5.8% of nano aluminum oxide, 1.5-2.2% of alkaline silica sol, 0.3-1% of nano silicon dioxide, 0.3-1% of nitride, 0.3-1% of curing agent, 8.1-12.1% of coupling agent, and 76-83% of solvent; the nano silicon dioxide is acid-leached, and the nitride is nano boron nitride and nano silicon nitride mixed in a weight ratio of 2:3. The alkaline silica sol is a silica sol with a content of 40wt%; the coupling agent may include but is not limited to one or more of a fluorine-containing silicone coupling agent, a fluorine-containing silane coupling agent, a fluorine-free silicone coupling agent, and a fluorine-free silane coupling agent; the solvent used includes but is not limited to an alcohol solvent, a benzene solvent, a carboxylic acid solvent, and water; the curing agent is a coating curing agent, and the present embodiment uses a siloxane curing agent; the acid leaching treatment mentioned in the present invention is to place the nano-silica to be treated in an acidic solution for treatment.
[0022] The preferred particle size range of the nano-powder used in the present invention is 400-500nm.
[0023] In some preferred embodiments, the acid leaching treatment is carried out by using a mixed acid of sulfuric acid and hydrofluoric acid, which can better treat the nano-silicon dioxide to increase its specific surface area and reduce its specific surface energy.
[0024] In some preferred embodiments, the concentrations of the sulfuric acid and the hydrofluoric acid are 15wt% and 10wt% respectively, the sulfuric acid and the hydrofluoric acid are mixed in a weight ratio of 1:1, the treatment time is 1-2 hours, and the treatment temperature is 50-80°C.
[0025] In some preferred embodiments, the coupling agent includes polydimethylsiloxane, α,ω-dihydroxypolysiloxane, hexamethyldisilazane, methyltrimethoxysilane, γ-aminopropyltriethoxysilane, [perfluoro(polypropoxy)]methoxypropyltrimethoxysilane.
[0026] In some preferred embodiments, the solvent includes n-butanol, xylene, water, anhydrous ethanol, and glacial acetic acid, and the solvent used is analytically pure.
[0027] In some preferred embodiments, the super-hydrophobic coating with radiative cooling comprises the following materials by mass fraction: 2% nano zinc oxide, 4% nano aluminum oxide, 2% alkaline silica sol, 1% nano silicon dioxide, 0.2% nano silicon nitride, 0.3% nano boron nitride, 0.9% curing agent, 7% polydimethylsiloxane, 0.5% α, ω-dihydroxypolysiloxane, 2% hexamethyldisilazane, 1.5% methyltrimethoxysilane, 0.6% γ-aminopropyltriethoxysilane, 8% n-butanol, 66% xylene, 1% water, 2% anhydrous ethanol, and 1% glacial acetic acid.
[0028] In some preferred embodiments, the nano boron nitride and nano silicon nitride are modified titanium dioxide-doped nano boron nitride and nano silicon nitride, and the preparation of the modified titanium dioxide-doped nano boron nitride and nano silicon nitride includes the following steps: step 1, mixing nano boron nitride, nano silicon nitride and nano titanium dioxide in a weight ratio of 10: 1-5, and then calcining at high temperature for 1-3 hours, adding n-hexane and anhydrous ethanol for stirring and ultrasonic dispersion to obtain suspension A, step 2, mixing suspension A with stearic acid in a reactor for reaction for 1-5 hours, separating and drying to obtain the modified titanium dioxide-doped nano boron nitride and nano silicon nitride. Nano boron nitride and nano silicon nitride are modified to have hydrophobicity, and at the same time, they are also wear-resistant, corrosion-resistant and high-temperature-resistant. When the coating is formed in the present invention, the synergistic modified silicon dioxide has passive radiation cooling performance and excellent super hydrophobic performance, and the wear resistance and acid and alkali corrosion resistance are significantly improved, thereby extending the service life of the coating.
[0029] In some preferred embodiments, the particle size of the nano-boron nitride and nano-silicon nitride is 0.5-3 μm.
[0030] In some preferred embodiments, the method for preparing the super hydrophobic coating with radiative cooling comprises:
[0031] S1. Place nano zinc oxide and nano aluminum oxide in a V-type mixer, prepare solution b with hexamethyldisilazane, water and ethanol, atomize solution b and add it to nano zinc oxide and nano aluminum oxide, react for 1-3 hours, and then dry to obtain modified powder, stirring continuously during the reaction;
[0032] S2, preparing alkaline silica sol and n-butanol into sol, uniformly dispersing by ultrasonic, dropping glacial acetic acid into the sol and dispersing by ultrasonic again, adding nano-silicon dioxide, nano-boron nitride, and nano-silicon nitride and dispersing by ultrasonic, adding α,ω-dihydroxypolysiloxane, methyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and reacting at 50-60° C. for 2-6 hours to obtain a mixed sol;
[0033] S3, uniformly mixing polydimethylsiloxane, the modified powder obtained in S1, and xylene, and dispersing them by ultrasonication, and then adding the mixed sol obtained in S2 and dispersing them by ultrasonication to obtain component A;
[0034] S4, mixing the curing agent as component B with component A evenly to obtain the super hydrophobic coating with radiation cooling. Component B is mixed with component A when in use, and the curing temperature is generally 80°C.
[0035] Unless otherwise defined herein, the scientific and technical terms used herein have the same meanings as those understood and commonly used by those skilled in the art.
[0036] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any particular theory or mechanism. In this article, all features defined in the form of numerical ranges or percentage ranges, such as quantity, value, concentration and content, are only for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have covered and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0037] The above features mentioned in the present invention or the features mentioned in the embodiments can be combined in any way. All features disclosed in this specification can be used in combination with any combination form, and as long as there is no contradiction in the combination of these features, all possible combinations should be considered to be within the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.
[0038] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages, ratios, proportions, or parts are by weight. The units mentioned in the weight percentages in the present invention are well known to those skilled in the art. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the recorded content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0039] Example 1
[0040] Preparation of super-hydrophobic coating with radiative cooling:
[0041] S1. Place 2kg of nano zinc oxide and 4kg of nano aluminum oxide in a V-type blender, prepare solution b with 2kg of hexamethyldisilazane, 1kg of water and 2kg of anhydrous ethanol, atomize solution b and add it to nano zinc oxide and nano aluminum oxide, react while stirring for 1h, and then dry to obtain modified powder;
[0042] S2, first prepare a mixed acid, mix 15wt% sulfuric acid and 10wt% hydrofluoric acid in a weight ratio of 1:1, mix 2kg of nano-silicon dioxide and 4kg of the mixed acid evenly for acid leaching, the treatment time is 1 hour, the treatment temperature is 50°C, the nano-silicon dioxide is separated from the mixed acid after treatment, the treated nano-silicon dioxide is washed with water 3 times, and finally dried to obtain acid-leached nano-silicon dioxide; then 2kg of alkaline silica sol and 8kg of n-butanol are prepared into a sol, ultrasonically dispersed evenly, 1kg of glacial acetic acid is dropped into the sol and ultrasonically dispersed again, 1kg of acid-leached nano-silicon dioxide, 0.2kg of nano-boron nitride, and 0.3kg of nano-silicon nitride are added for ultrasonic dispersion, 0.5kg of α, ω-dihydroxy polysiloxane, 1.5kg of methyltrimethoxysilane, and 0.6kg of γ-aminopropyltriethoxysilane are added, and the reaction is carried out at 50°C for 2h to obtain a mixed sol;
[0043] S3, 7 kg of polydimethylsiloxane, the modified powder obtained in S1, and 66 kg of xylene are mixed evenly, and ultrasonically dispersed, and then the mixed sol obtained in S2 is added and ultrasonically dispersed evenly to obtain component A;
[0044] S4. Mix 0.9 kg of curing agent as component B and component A evenly to obtain a super hydrophobic coating with radiation cooling.
[0045] Example 2
[0046] Preparation of super-hydrophobic coating with radiative cooling:
[0047] S1. Place 2kg of nano zinc oxide and 4kg of nano aluminum oxide in a V-type mixer, prepare solution b with 2kg of hexamethyldisilazane, 1kg of water and 2kg of anhydrous ethanol, atomize solution b and add it to nano zinc oxide and nano aluminum oxide, react while stirring for 1h, and then dry to obtain modified powder;
[0048] S2, first prepare mixed acid, mix 15wt% sulfuric acid and 10wt% hydrofluoric acid in a weight ratio of 1:1, mix 2kg of nano silicon dioxide and 4kg of mixed acid evenly for acid leaching, the treatment time is 1 hour, the treatment temperature is 50°C, the nano silicon dioxide is separated from the mixed acid after treatment, the treated nano silicon dioxide is washed with water 3 times, and finally dried to obtain acid-leached nano silicon dioxide; select 0.4kg of nano boron nitride and 0.6kg of nano silicon nitride with a particle size of 0.5-3μm, mix 0.5kg of nano boron nitride, 0.5kg of nano silicon nitride and 0.1kg of nano titanium dioxide, and then calcine at high temperature for 1 hour, then add 2kg of n-hexane and 2kg of k g of anhydrous ethanol is stirred and ultrasonically dispersed to obtain a suspension A, the suspension A is mixed with stearic acid in a reactor to react for 1 hour, and separated and dried to obtain modified titanium dioxide-doped nano boron nitride and nano silicon nitride; 2kg of alkaline silica sol and 8kg of n-butanol are configured into a sol, and ultrasonically dispersed uniformly, 1kg of glacial acetic acid is dropped into the sol and ultrasonically dispersed again, 1kg of acid-leached nano silicon dioxide, 0.5kg of modified titanium dioxide-doped nano boron nitride, and nano silicon nitride are added and ultrasonically dispersed, 0.5kg of α, ω-dihydroxy polysiloxane, 1.5kg of methyltrimethoxysilane, and 0.6kg of γ-aminopropyltriethoxysilane are added, and the mixture is reacted at 50° C. for 2h to obtain a mixed sol;
[0049] S3, 7 kg of polydimethylsiloxane, the modified powder obtained in S1, and 66 kg of xylene are mixed evenly, and ultrasonically dispersed, and then the mixed sol obtained in S2 is added and ultrasonically dispersed evenly to obtain component A;
[0050] S4. Mix 0.9 kg of curing agent as component B and component A evenly to obtain a super hydrophobic coating with radiation cooling.
[0051] Example 3
[0052] Preparation of super-hydrophobic coating with radiative cooling:
[0053] S1. Place 1.8 kg of nano zinc oxide and 5 kg of nano aluminum oxide in a V-type blender, prepare solution b with 1.8 kg of hexamethyldisilazane, 0.9 kg of water and 1.7 kg of anhydrous ethanol, atomize solution b and add it to nano zinc oxide and nano aluminum oxide, react while stirring for 3 hours, and then dry to obtain modified powder;
[0054] S2, first prepare mixed acid, mix 15wt% sulfuric acid and 10wt% hydrofluoric acid in a weight ratio of 1:1, mix 1.5kg nano silicon dioxide and 3kg mixed acid evenly for acid leaching, the treatment time is 2 hours, the treatment temperature is 80°C, the nano silicon dioxide is separated from the mixed acid after treatment, the treated nano silicon dioxide is washed with water 3 times, and finally dried to obtain acid-leached nano silicon dioxide; select 0.6kg nano boron nitride and 0.9kg nano silicon nitride with a particle size of 0.5-3μm, mix 0.6kg nano boron nitride, 0.9 nano silicon nitride and 0.5kg nano titanium dioxide, and then high-temperature roast for 3 hours, add 3kg n-hexane and 3kg anhydrous ethanol and stir for ultraviolet light. Acoustic dispersion is performed to obtain suspension A, and the suspension A is mixed with 1.5 kg of stearic acid in a reactor to react for 5 hours, and the nano boron nitride and nano silicon nitride doped with modified titanium dioxide are separated and dried to obtain; 1.8 kg of alkaline silica sol and 8.6 kg of n-butanol are then configured into a sol, and ultrasonic dispersion is performed uniformly, 0.5 kg of glacial acetic acid is added dropwise to the sol and ultrasonic dispersion is performed again, 0.7 kg of acid-leached nano silicon dioxide, 0.5 kg of modified nano boron nitride and nano silicon nitride doped with titanium dioxide are added and ultrasonic dispersion is performed, 0.4 kg of α, ω-dihydroxy polysiloxane, 1.4 kg of methyltrimethoxysilane, and 0.2 kg of γ-aminopropyltriethoxysilane are added, and the mixture is reacted at 50-60° C. for 2-6 hours to obtain a mixed sol;
[0055] S3, 6.8 kg of polydimethylsiloxane, the modified powder obtained in S1, and 67 kg of xylene were mixed evenly, and ultrasonically dispersed, and then the mixed sol obtained in S2 was added and ultrasonically dispersed evenly to obtain component A;
[0056] S4. Mix 0.9 kg of curing agent as component B and component A evenly to obtain a super hydrophobic coating with radiation cooling.
[0057] Example 4
[0058] Preparation of super-hydrophobic coating with radiative cooling:
[0059] S1. Place 2.2 kg of nano zinc oxide and 5.5 kg of nano aluminum oxide in a V-type mixer, prepare solution b with 2.3 kg of hexamethyldisilazane, 1.2 kg of water and 2 kg of anhydrous ethanol, atomize solution b and add it to nano zinc oxide and nano aluminum oxide, react while stirring for 2 hours, and then dry to obtain modified powder;
[0060] S2, first prepare mixed acid, mix 15wt% sulfuric acid and 10wt% hydrofluoric acid in a weight ratio of 1:1, mix 1.5kg nano silicon dioxide and 3kg mixed acid evenly for acid leaching, the treatment time is 2 hours, the treatment temperature is 50-80℃, after treatment, separate the nano silicon dioxide from the mixed acid, wash the treated nano silicon dioxide with water 3 times, and finally dry to obtain acid-leached nano silicon dioxide; select 0.6kg nano boron nitride and 0.9kg nano silicon nitride with a particle size of 0.5-3μm, mix 0.6kg nano boron nitride, 0.9kg nano silicon nitride and 0.45kg nano titanium dioxide, and then calcine at high temperature for 2 hours, add 3kg n-hexane and 3kg inorganic Stir and ultrasonically disperse water and ethanol to obtain suspension A, mix suspension A with 3kg of stearic acid in a reactor and react for 4 hours, separate and dry to obtain modified titanium dioxide-doped nano boron nitride and nano silicon nitride; then prepare sol with 2.2kg of alkaline silica sol and 8.9kg of n-butanol, ultrasonically disperse evenly, drop 0.9kg of glacial acetic acid into the sol and ultrasonically disperse again, add 1kg of acid-leached nano silicon dioxide, 0.8kg of modified titanium dioxide-doped nano boron nitride and nano silicon nitride and ultrasonically disperse, add 0.7kg of α, ω-dihydroxy polysiloxane, 1.5kg of methyltrimethoxysilane and 0.4kg of γ-aminopropyltriethoxysilane, react at 55°C for 5h to obtain a mixed sol;
[0061] S3, 7.4 kg of polydimethylsiloxane, the modified powder obtained in S1, and 62 kg of xylene were mixed evenly, and ultrasonically dispersed, and then the mixed sol obtained in S2 was added and ultrasonically dispersed evenly to obtain component A;
[0062] S4. Mix 1 kg of curing agent as component B and component A evenly to obtain a super hydrophobic coating with radiation cooling.
[0063] Comparative Example 1
[0064] In Example 1, the step of "preparing a mixed acid by mixing 15 wt % sulfuric acid and 10 wt % hydrofluoric acid in a weight ratio of 1:1, uniformly mixing 1.5 kg of nano-silicon dioxide and 3 kg of the mixed acid for acid leaching, the treatment time is 2 hours, the treatment temperature is 80°C, after the treatment, the nano-silicon dioxide is separated from the mixed acid, the treated nano-silicon dioxide is washed with water 3 times, and finally dried to obtain the acid-leached nano-silicon dioxide" is reduced, and the other steps are the same as in Example 1.
[0065] Comparative Example 2
[0066] In Example 1, "0.2 kg of nano-boron nitride and 0.3 kg of nano-silicon nitride" are not added to S2, and the other steps are the same as those in the example.
[0067] Comparative Example 3
[0068] In Example 1, the step of "preparing a mixed acid by mixing 15wt% sulfuric acid and 10wt% hydrofluoric acid in a weight ratio of 1:1, uniformly mixing 1.5kg of nano-silicon dioxide and 3kg of the mixed acid for acid leaching, the treatment time is 2 hours, the treatment temperature is 80°C, after the treatment, the nano-silicon dioxide is separated from the mixed acid, the treated nano-silicon dioxide is washed with water 3 times, and finally dried to obtain the acid-leached nano-silicon dioxide" is reduced; "0.2kg of nano-boron nitride and 0.3kg of nano-silicon nitride" are not added in S2, and the other steps are the same as those in the example.
[0069] Comparative Example 4
[0070] In Example 1, "0.5 kg of nano boron nitride" is added to S2, and the other steps are the same as those in the example.
[0071] Comparative Example 5
[0072] In Example 1, "0.5 kg of nano silicon nitride" is added to S2, and the other steps are the same as those in the example.
[0073] Preparation of coating: The coating was coated on a glass substrate and cured to obtain a coating of about 0.2 mm. The super-hydrophobic coatings with radiative cooling prepared in Examples 1-4 and Comparative Examples 1-5 were made into coatings according to the above method and used as samples to test their performance.
[0074] The test conditions or test standards for each performance test item are as follows:
[0075] Contact angle: A 5 μL droplet (water contact angle is deionized water) is vertically dropped onto the flat coating surface and measured using a contact angle meter.
[0076] Sunlight reflectivity: Test the reflectivity in the 300-2500nm band using a UV-visible spectrometer.
[0077] Infrared emissivity: Test the infrared emissivity of the 8–13 μm atmospheric transparent window using a Fourier infrared spectrometer with an integrating sphere (calculate the emissivity based on Kirchhoff’s law, the emissivity of an opaque object = 1-reflectivity).
[0078] Acid resistance test: Use 1mol / L hydrochloric acid solution, the coating is completely exposed to the hydrochloric acid solution, immersed for 24 hours, and the coating water contact angle, solar reflectivity, and infrared reflectivity are tested.
[0079] Alkali resistance test: Use 1mol / L sodium hydroxide solution, the film layer is completely in contact with the sodium hydroxide solution, immersed for 24 hours, and the coating water contact angle, solar reflectivity, and infrared reflectivity are tested.
[0080] Wear resistance test: Use an abrasion tester to rotate the sample 200 times to test the coating's water contact angle, solar reflectivity, and infrared reflectivity.
[0081] Table 1: Solar reflectivity of the coatings prepared in Examples 1-4 and Comparative Examples 1-5 before and after acid resistance, alkali resistance, and abrasion resistance tests
[0082] Before the test After acid resistance test After alkali resistance test After wear test Example 1 91% 85% 87% 87% Example 2 92% 90% 91% 91% Example 3 91% 90% 89% 90% Example 4 92% 90% 90% 91% Comparative Example 1 85% 79% 81% 85% Comparative Example 2 88% 72% 74% 62% Comparative Example 3 81% 68% 73% 60% Comparative Example 4 89% 84% 86% 78% Comparative Example 5 89% 86% 85% 77%
[0083] Table 2: Infrared emissivity of the coatings prepared in Examples 1-4 and Comparative Examples 1-5 before and after acid resistance, alkali resistance, and wear resistance tests
[0084] Before the test After acid resistance test After alkali resistance test After wear test Example 1 91% 87% 85% 88% Example 2 94% 91% 92% 91% Example 3 93% 91% 91% 91% Example 4 95% 92% 91% 92% Comparative Example 1 85% 76% 73% 85% Comparative Example 2 88% 73% 74% 61% Comparative Example 3 82% 65% 62% 59% Comparative Example 4 88% 82% 83% 75% Comparative Example 5 89% 81% 80% 76%
[0085] Table 3: Water contact angles of the coatings prepared in Examples 1-4 and Comparative Examples 1-5 before and after acid resistance, alkali resistance, and wear resistance tests
[0086] Before the test After acid resistance test After alkali resistance test After wear test Example 1 150° 135° 136° 134° Example 2 153° 149° 147° 143° Example 3 152° 150° 146° 143° Example 4 152° 146° 148° 145° Comparative Example 1 128° 113° 114° 119° Comparative Example 2 132° 109° 110° 97° Comparative Example 3 120° 91° 89° 88° Comparative Example 4 139° 119° 121° 111° Comparative Example 5 138° 117° 119° 113°
[0087] It can be seen from the test results of Table 1, Table 2 and Table 3 that the coating of the present invention has good super-hydrophobic performance, has excellent passive radiation refrigeration function, and has good acid and alkali corrosion resistance, especially excellent wear resistance. 1. From Example 1 and Example 2, it can be seen that the super-hydrophobic coating of nano-silicon nitride and nano-boron nitride after modification is more resistant to acid and alkali corrosion, more wear-resistant, and the effect is obvious; 2. From the test results of Example 1, Comparative Example 4 and Comparative Example 5, it can be seen that the present invention adds nano-silicon nitride and nano-boron nitride synergistically, so that the acid and alkali corrosion resistance and wear resistance of the coating of the present invention are significantly better than the acid and alkali corrosion resistance and wear resistance of nano-silicon nitride or nano-boron nitride added alone.
[0088] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A super hydrophobic coating with radiative cooling, characterized in that, The super hydrophobic coating with radiative cooling comprises the following materials in mass fraction: 1.5-2.2% of nano zinc oxide, 3.9-5.8% of nano aluminum oxide, 1.5-2.2% of alkaline silica sol, 0.3-1% of nano silicon dioxide, 0.3-1% of nitride, 0.3-1% of curing agent, 8.1-12.1% of coupling agent, and 76-83% of solvent; the nano silicon dioxide is acid-leached, and the nitride is a mixture of nano boron nitride and nano silicon nitride in a weight ratio of 2:
3.
2. The super-hydrophobic coating with radiative cooling as claimed in claim 1, characterized in that, The acid leaching treatment is carried out by using a mixed acid of sulfuric acid and hydrofluoric acid.
3. The super-hydrophobic coating with radiative cooling as claimed in claim 3, characterized in that, The concentrations of the sulfuric acid and the hydrofluoric acid are 15wt% and 10wt% respectively, and the sulfuric acid and the hydrofluoric acid are mixed in a weight ratio of 1:
1. The treatment time is 1-2 hours and the treatment temperature is 50-80°C.
4. The super-hydrophobic coating with radiative cooling as claimed in claim 1, characterized in that, The coupling agent includes polydimethylsiloxane, α,ω-dihydroxypolysiloxane, hexamethyldisilazane, methyltrimethoxysilane, γ-aminopropyltriethoxysilane, and [perfluoro(polypropoxy)]methoxypropyltrimethoxysilane.
5. The super-hydrophobic coating with radiative cooling as claimed in claim 1, characterized in that, The solvent includes n-butanol, xylene, water, anhydrous ethanol and glacial acetic acid.
6. The super-hydrophobic coating with radiative cooling as claimed in claim 1, characterized in that, The super-hydrophobic coating with radiation cooling is made of the following materials by mass fraction: 2% of nano zinc oxide, 4% of nano aluminum oxide, 2% of alkaline silica sol, 1% of nano silicon dioxide, 0.2% of nano silicon nitride, 0.3% of nano boron nitride, 0.9% of curing agent, 7% of polydimethylsiloxane, 0.5% of α, ω-dihydroxy polysiloxane, 2% of hexamethyldisilazane, 1.5% of methyltrimethoxysilane, 0.6% of γ-aminopropyltriethoxysilane, 8% of n-butanol, 66% of xylene, 1% of water, 2% of anhydrous ethanol, and 1% of glacial acetic acid.
7. The super-hydrophobic coating with radiative cooling as claimed in claim 1, characterized in that, The nano boron nitride and nano silicon nitride are nano boron nitride and nano silicon nitride modified by doping titanium dioxide. The preparation of the nano boron nitride and nano silicon nitride modified by doping titanium dioxide includes the following steps: step 1, mixing nano boron nitride, nano silicon nitride and nano titanium dioxide in a weight ratio of 10:1-5, and then calcining at high temperature for 1-3 hours, adding n-hexane and anhydrous ethanol to stir and ultrasonically disperse to obtain suspension A; step 2, mixing suspension A with stearic acid in a reactor to react for 1-5 hours, separating and drying to obtain the modified nano boron nitride and nano silicon nitride doped with titanium dioxide.
8. The preparation method of the super-hydrophobic coating with radiation cooling as claimed in claim 7, characterized in that, The particle size of the nano silicon nitride and nano boron nitride is 0.5-3 μm.
9. the preparation method of the super-hydrophobic coating with radiation cooling as claimed in claim 6, is characterized in that, The preparation method of the super hydrophobic coating with radiative cooling comprises: S1. Place nano zinc oxide and nano aluminum oxide in a V-type mixer, prepare solution b with hexamethyldisilazane, water and ethanol, atomize solution b and add it into nano zinc oxide and nano aluminum oxide, react for 1-3 hours, and then dry to obtain modified powder; S2, preparing alkaline silica sol and n-butanol into sol, uniformly dispersing by ultrasonic, dropping glacial acetic acid into the sol and dispersing by ultrasonic again, adding nano-silicon dioxide, nano-boron nitride, and nano-silicon nitride and dispersing by ultrasonic, adding α,ω-dihydroxypolysiloxane, methyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and reacting at 50-60° C. for 2-6 hours to obtain a mixed sol; S3, uniformly mixing polydimethylsiloxane, the modified powder obtained in S1, and xylene, and dispersing them by ultrasonication, and then adding the mixed sol obtained in S2 and dispersing them by ultrasonication to obtain component A; S4. Mixing the curing agent as component B and component A uniformly to obtain the super-hydrophobic coating with radiation cooling.
Citation Information
Patent Citations
Radiation refrigeration coating with stain resistance and preparation method thereof
CN118994983A
Cited By
Inorganic radiation refrigeration coating with zinc tailings-prepared secondary zinc oxide as filler, coating and preparation method of inorganic radiation refrigeration coating
CN121406166A